KARAKTERISTIK PASIEN OSTEOARTRITIS DI POLIKLINIK ORTOPEDI RS ROYAL PRIMA MEDAN - Liena Liena (Universitas Prima Indonesia, 2021)
Osteoarthritis is a degenerative joint disease caused by the breakdown of joint cartilage, usually occurs in the spine, hips, knees, and ankles. This study aims to determine Overview Osteoarthritis Patient Characteristics Polyclinic Prima Royal Orthopaedic Hospital Medan. This study is a descriptive retrospective case study design with a sample of 100 samples were taken by purposive sampling is the most complete data. This study, obtained the highest age group 56-65 years of age by the amount of 41% by 41 people. Meanwhile, the lowest number in the 26-35 year age. This study, obtained the highest age group 56-65 years of age by the amount of 41% by 41 people. Meanwhile, the lowest number in the 26-35 year age that is 1% (1 people). Most gender is female 70% (70 people). Most jobs are housewives is 44% (44 people). Patients with a genetic history are 78% (78 people). Based on the largest weight factor is obese or overweight with 74% (74 people). The main complaint is joint pain as much as 100% (100 people). The most additional complaint is morning stiffness is 75% (75 people). Distribution of osteoarthritis patients based on the results of investigations that most anatomical changes occur joints by 77% (77 people). In Osteoarthritis patients are encouraged to maintain a healthy weight ideal and there should be an outreach to the community about Osteoarthritis society as much as possible in order to avoid factors originators.